Recurrent posterior fossa intracranial capillary hemangioma in a pregnant woman: A case report and review of literature. (December 2022) - Abouei Mehrizi, Mohammad Ali; Baharvahdat, Humain; Saghebdoust, Sajjad
Abstract: Introduction: Intracranial capillary hemangioma (ICH) is a rare tumor with a slightly higher incidence in women. Surgical management of ICH during pregnancy requires a joint decision, for it has been a contentious issue owing to the inadequate number of cases. Presentation of case: A 23-year-old female with an ICH in the posterior fossa underwent subtotal tumor resection (STR). One year later, she was referred to the neurosurgery department in the 8th week of pregnancy due to a progressive headache, vomit, and a bulging occipital mass. Subsequent to an abortion, preoperative angiography and Bleomycin injection were performed, and the tumor was totally resected thereafter. Over a one-year follow-up, her symptoms faded, and she experienced no recurrence. Discussion: ICH, a highly vascular entity, poses a substantial intraoperative bleeding risk. During the first surgery, intraoperative bleeding deterred the surgeon from a gross total resection (GTR), leading to a recurrence due to the growth of residual tissue during pregnancy. Having aborted the fetus, the patient underwent angioembolization to lessen the risk of intraoperative bleeding before reoperation, rendering it more possible for the surgeon to achieve GTR. Accordingly, quality of resection and a multidisciplinary approach is necessary to ensure optimal treatment. Conclusion: There is a growing consensus that not only is STR a contributory factor in ICH recurrence, but female hormones and increased cardiac output in pregnancy might play a pivotal role in the progression of the tumor. Thus, paying further attention to pregnant or peripartum patients with suspected ICH should assume greater significance. Highlights: ICH is a scarce tumor with a moderately higher incidence in women. The treatment's cornerstone is GTR, which can lessen the risk of recurrence. ICH can recur during pregnancy due to hormonal changes and unknown growth factors. It is wise to pay more attention to pregnant patients harboring a suspected ICH. This is the first case of recurrent ICH due to an unplanned pregnancy.